Detection of different enteric viruses in children with diarrheal disease: evidence of the high frequency of mixed infections. Issue 2 (29th March 2019) - Tatte, Vaishali S.; Gopalkrishna, Varanasi
Abstract : Enteric viruses play a major role in causing diarrhea in children. Early identification of the causative pathogen is still a challenge in the clinical laboratory. A multiplex PCR assay is a useful tool to screen a large number of clinical samples especially in an outbreak situation. In this study, a multiplex reverse transcription (RT)-PCR assay was developed to detect nine enteric viruses such as group A rotavirus, norovirus GGII, sapovirus, adenovirus, astrovirus, aichivirus, parechovirus, bocavirus and enterovirus in clinical samples of diarrheal cases. Stool samples ( n =185) collected from infants and children with acute gastroenteritis cases in Pune, western India were analysed for nine different enteric viruses by currently developed multiplex RT- PCR. Predominance of group A rotavirus (76%) followed by enterovirus (11.5%), astrovirus (4.5%), adenovirus (2.7%) and norovirus GII (1.6%) was observed. A total of 44.8 % (82/185) samples analysed by this method showed high frequency of mixed infections. These results highlighted high prevalence and diversity of different enteric viruses in children. The multiplex PCR showed good concordance with monoplex RT-PCR for detection of these enteric viruses in clinical samples. This is the first report on the development of a multiplex RT-PCR assay for detection of multiple enteric viruses in diarrheal diseases from India.